The theology of the shorter Pauline letters - Donfried, Karl P.; Marshall, I. Howard (Cambridge [England] ; New York, NY, USA : Cambridge University Press, 1993)
This book breaks new ground in offering an exposition of the theological message of the Shorter Pauline Letters. Karl P. Donfried puts 1 and 2 Thessalonians in their cultural context, and identifies a number of key themes in these letters, such as the notion of election. I. Howard Marshall's study of Philippians brings out especially the understanding of the theological basis of the Christian life that underlies the letter, while his discussion of Philemon emphasizes how the main theme of the letter is the relation between the gospel and Christian ethics.
Editor's preface -- List of abbreviations -- The theology of I Thessalonians / Karl P. Donfried: 1. The setting of 1 Thessalonians -- 2. The theology of 1 Thessalonians -- 3. 1 Thessalonians, the Pauline corpus and Acts -- 4. The significance of I Thessalonians for today -- The theology of 2 Thessalonians / Karl P. Donfried: 5. The setting of 2 Thessalonians --6. The theology of 2 Thessalonians -- 7. 2 Thessalonians and the New Testament -- 8. The significance of 2 Thessalonians for today -- The theology of Philippians / I. Howard Marshall: 9. Exploring the building site -- 10. Laying the foundation -- 11. Building the walls -- 12. The shape of the Church -- 13. Philippians and its architect -- 14. A building that still stands -- The theology of Philemon / I. Howard Marshall: 15. The Gospel and slavery -- Bibliography -- Indexes.
Includes bibliographical references (pages 192-195) and indexes.
Keywords: Bible. -- Theology; Bible. -- Theology; Bible. -- Theology